An infrequent complication of a not so infrequent disease. Hit by HIT. (February 2019) - Sandoval, Elena; Ascaso, María; Quintana, Eduard; Pereda, Daniel
Heparin-induced thrombocytopenia is not uncommon in cardiac surgery. Thrombosis is the most frequent complication. A 77-year-old man suffered cardiac arrest due to right coronary emboli. Transesophageal echocardiography revealed tissue valve thrombosis. He required support with an extracorporeal membrane oxygenator that also thrombosed. Heparin-induced thrombocytopenia was diagnosed, and anticoagulation was switched to argatroban. Heparin- induced thrombocytopenia normally presents as vascular thrombosis. In this case, the first symptom was tissue valve thrombosis causing an acute coronary syndrome. It is not an uncommon complication and should be considered if unexpected thrombosis and a sudden drop in platelet count develops after heparin exposure.